2022
DOI: 10.1039/d2ta90050e
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress and perspectives on single-atom catalysis

Abstract: Zhiqun Lin, María Escudero-Escribano and Jun Li introduce the Journal of Materials Chemistry A themed issue on single-atom catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Single-atom catalysts (SACs) have achieved significant progress in heterogeneous catalysis, such as CO oxidation, the water-gas shift reaction, electrocatalytic reactions, etc., owing to their efficiency in full atom utilization and excellent activity. 243,[250][251][252][253] As shown in Fig. 20a, the three important compositions in the SACs are the metal central ions, the surrounding ligands, and the host materials.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Single-atom catalysts (SACs) have achieved significant progress in heterogeneous catalysis, such as CO oxidation, the water-gas shift reaction, electrocatalytic reactions, etc., owing to their efficiency in full atom utilization and excellent activity. 243,[250][251][252][253] As shown in Fig. 20a, the three important compositions in the SACs are the metal central ions, the surrounding ligands, and the host materials.…”
Section: 3mentioning
confidence: 99%
“…, owing to their efficiency in full atom utilization and excellent activity. 243,250–253 As shown in Fig. 20a, the three important compositions in the SACs are the metal central ions, the surrounding ligands, and the host materials.…”
Section: Key Components Of Aem Water Electrolyzers and Fuel Cellsmentioning
confidence: 99%
“…In consequence, they are extensively employed as heterogeneous catalysts in photocatalytic CO 2 reduction reactions. 165,166 Herein, we distinctively feature transition metal SACs promoting CO 2 photo-reduction to syngas. Wang et al 51 demonstrated room-temperature synthesis of Fe single atoms anchored over nitrogen doped porous carbon support (denoted as Fe-SAs/N-C) via an electro-chemical filtration method for CO 2 photoreduction into tuneable syngas.…”
Section: Single-atom Photocatalyst For Syngas Productionmentioning
confidence: 99%
“…The appropriate support effect can not only stabilize the single atom site but also accelerate mass transport and charge transfer [45,46]. SACs have made important progress in catalyzing single-molecule elementary reactions, such as HER and oxygen evolution reaction (OER) [47,48]. The simplicity of active sites makes SACs weak in catalyzing complex multiple-molecule reactions.…”
Section: Introductionmentioning
confidence: 99%